PENGEMBANGAN MEDIA KOMIK KERAGAMAN BUDAYA BERBASIS CANVA UNTUK MENINGKATKAN KREATIVITAS DAN SIKAP NASIONALISME SISWA SD - Prahastiwi, Linda; Qisti Barriyah, Insanul; Wibawa, Sutrisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to produce Canva-based cultural diversity comic media, determine the feasibility and effectiveness of Canva-based cultural diversity comic media in increasing creativity and nationalistic attitudes in fourth grade elementary school students. Development research was carried out using the ADDIE model (Analysis, Design, Develop, Implement, Evaluate). Based on the results of research and development, it shows that (1) learning comic media is suitable for use in learning. According to material experts and learning media experts, comic media products are in the